Efektifitas Penerapan Terapi Mendengarkan Murrotal Terhadap Tekanan Darah Pada Penderita Hipertensi Di Perumahan Kelapa Gading Dusun II Keramat Sakti - Zulfana, Diana; Elka Fitri, Dwi; Ulfah Ayudytha, Awaliyah; Akbar, Aulya (JURNAL PENDIDIKAN KESEHATAN, 2024)
Hypertension is a condition where a person experiences an increase in blood pressure above normal, which is equal to or more than 140/90 mmHg. Management of hypertension is divided into two parts, namely pharmacological and non-pharmacological. One of the non-pharmacological management is murottal Qur'an therapy. The sound produced in murottal Qur'an therapy can make you feel relaxed and affect blood pressure in hypertension. The surah of the Koran used in this study is the surah Ar-Rahman. Method: this application involves 5 subjects with the criteria of Willing to be respondents, Muslim, male or female, old adults (35-45 years), no hearing loss, and primary hypertension with systolic blood pressure > 140 mmHg and blood pressure diastolic > 90 mm Hg. Discussion: The application of murottal Qur'an therapy to blood pressure in hypertensive patients can occur because of the sound produced in reading the Qur'an. Conclusion: Based on the results of applying murottal Qur'an therapy to reducing blood pressure in hypertensive patients, the authors conclude that there is a change in blood pressure reduction in murrotal therapy for 5 hypertensive patients, which was carried out for 7 days in Kelapa Gading housing, Keramat Sakti II hamlet, Kubang Jaya.